DOI: 10.1007/978-3-540-69248-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Content and Delivery Across Tobacco Products

Abstract: Nicotine is the principal alkaloid in both commercial and homemade products (e.g., cigarettes, smokeless tobacco, bidis, waterpipes) followed by nornicotine, anabasine, anatabine, and many other basic substances that contain a cyclic nitrogenous nucleus. Tobacco types, leaf position on the plant, agricultural practices, fertilizer treatment, and degree of ripening are among some prominent factors that determine the levels of alkaloids in tobacco leaf. From a random examination of 152 cultivated varieties of Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 60 publications
2
57
0
1
Order By: Relevance
“…First, little is known about the health risks of RYO tobacco use relative to FM cigarettes. Standard machine-determined yields of RYO cigarettes suggest that RYO smokers may be exposed to higher levels of smoke constituents per cigarette compared with smokers of FM cigarettes (Darrall & Figgins, 1998;Djordjevic, 2004;Dymond, 1996;Kaiserman & Rickert, 1992). However, given that estimates of exposure were made using variants of standardized puffing regimes that do not accurately reflect human exposures (Hammond et al, 2007), the possible adverse health effects remain pure speculation.…”
Section: Discussionmentioning
confidence: 99%
“…First, little is known about the health risks of RYO tobacco use relative to FM cigarettes. Standard machine-determined yields of RYO cigarettes suggest that RYO smokers may be exposed to higher levels of smoke constituents per cigarette compared with smokers of FM cigarettes (Darrall & Figgins, 1998;Djordjevic, 2004;Dymond, 1996;Kaiserman & Rickert, 1992). However, given that estimates of exposure were made using variants of standardized puffing regimes that do not accurately reflect human exposures (Hammond et al, 2007), the possible adverse health effects remain pure speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Other minor alkaloids include nornicotine, anatabine, and anabasine. 14 The amount of total and free (unprotonated, base) nicotine varies substantially among ST products (Table 2). Nicotine concentration is determined by manufacturing/blending strategies, types of tobacco (eg, Maryland versus Turkish), product design features (dry versus moist), and the type and amount of additives.…”
Section: Chemical Composition Of St Productsmentioning
confidence: 99%
“…The lowest content was found in T66, which had less than 60% of the total alkaloids content found in NC297. From a random examination of 152 cultivars of Nicotiana tabacum, Djordjevic and Doran (2009) found a range of alkaloid contents between 1.7 and 49.3 mg/g. Our results showed that the total alkaloids content in N. tabacum was obviously higher than that in N. tomentosiformis (Table 2).…”
Section: Alkaloid Contentmentioning
confidence: 99%
“…However, each step in the processing of tobacco leaves that affects plant metabolism may result in changes in the alkaloid content to a certain degree (Djordjevic and Doran, 2009). Djordjevic et al (1989) found that the contents of nicotine, nornicotine, anatabine, and anabasine increased in NC95 from harvesting through curing.…”
Section: Alkaloid Contentmentioning
confidence: 99%